Pediatric Kidney Transplantation: Frameshift in Medical and Surgical Management. Does the Perioperative Setting Have an Impact on Transplant Outcome? A Single-Center Experience - Bergel, Berenice; Geppert, Tamara; Bañuelos Marco, Beatriz; Friedersdorff, Frank; Müller, Dominik; Kempf, Caroline; Lachmann, Nils; Lingnau, Anja (Frontiers in Surgery, 2022)
Introduction Frameshift in medical management as well as in surgical thinking is putting the patient as a whole is the focus, rather than just the disease. To optimize the treatment of our pediatric transplant patients in our institution, we changed in 2013 the transplant program setting, treating, and operating all patients with pediatric transplant exclusively in a pediatric environment. The aim of this study was to analyze whether or not this change had an impact on patients safety, patient population, and patients and transplant outcome. Methods In the retrospective analysis, we compared transplant outcome of two eras. Era1 (2008–2012) solely included patients treated in the adult facilities, era 2 (2013–2017) patients were exclusively treated in the pediatric environment. Results There were 53 patients with renal transplant, with era 1 (28 patients) and era 2 (25 patients). Overall mortality was 5.6%. Median recipient age at transplantation was 13.2 years in era 1 and 8.59 years in era 2, median recipient weight at transplantation was 41.7 kg in era 1 vs. 26 kg in era 2, median size 149. 5 cm (era 1) vs. 123 cm in era2 (p = 0.05). The direct recipient/donor weight ratio remained stable in both eras, for recipients below 20 kg we saw a larger weight mismatch in era 1 (0.84 vs. 0.66). In the subgroup of patients with congenital anomalies of the kidney and urinary tract (CAKUT) those were significantly younger at onset of dialysis (p < 0.001) and at time of transplantation (p < 0.001), also they were less in body weight (p < 0.01), and body size (p < 0.001), this subgroup was larger in era 2. HLA mismatch data, serum creatinine, and GFR yield comparable results in both groups. Median time to detection of DSA was 46.2 month (3.8 years). Conclusion Since children with ESRD at the time of transplant trend to be younger and smaller, it is crucial to ensure a medical environment that is able to address their particular challenges. Even in this recipient cohort, renal transplantation can be performed safely as outlined by our data.